Voice,Data,Video integratıon and its applications in enterprises - Şan, Ömür Atakan (My University, 1999)
İçinde bulunduğumuz bilgi çağındaki modern organizasyonlar; ses, veri, ve video iletişimini altyapılarında entegre etmenin büyük avantajlarını keşfetmektedirler. Ses, veri ve video iletişimini destekleyen altyapılar ve uygulamalar sadece işletmelerin iş yapış şekillerini değiştirmekle kalmayıp; bu entegrasyonu kullanan işletmelere rekabet avantajları da sağlamaktadır. Bu tezin amacı ses, veri ve video entegrasyonunu incelemek ve işletmelerde kullanılabilir uygulamaları keşfetmektir. Çokluortam uygulamaları, ses ve videonun sadece veri taşıyan alışılagelmiş veri ağlarına entegrasyonu; ses, veri ve video bilgilerini tek bir ağda birleştiren çoklu servis ağlarının ortaya çıkışını sağlamıştır. Bu gelişmeler paralelinde ses, veri ve video ağları tek bir ağ üzerinde birleşmektedir. Bu entegrasyon sayesinde işletmeler ses, veri ve video iletişimi için birbirinden bağımsız üç ağ kurmaktan kurtulmaktadırlar. Ses, veri ve video bilgilerinin ortak bir ağda taşınması işletmelere büyük yararlar sağlamaktadır. Bu tezde ses, veri ve video entegrasyonunu sağlayan teknolojiler tartışılmaktadır. Ses, veri ve video uygulamalarının özellikleri, gelişen standartlar ve pazarlar adreslenmektedir. Tezin sonunda da gerçekleştirilmiş bir projenin yardımıyla; ses, veri ve video entegrasyonunun finansal avantajları ortaya konmaktadır.

Modern organizations in the information age are dramatically discovering the great benefits of deploying voice, data and video integration in their communication infrastructure. The deployment of infrastructures and applications consisting the combination of voice, data and video is not only fundamentally transforming the manner in which business is conducted but also giving competitive advantages to the companies which have deployed them. The objective of this thesis is to carry out a research on voice, data and video integration and discover the relevant applications in enterprises. Multimedia applications and the integration of voice and video onto traditional data-only networks are fueling the emergence of the multiservice network that is capable of integrating data, voice, and video onto a single network. Voice,data and video networks are being integrated. Enterprises are getting rid of three separate networks dedicated for carrying voice, data and video respectively by this integration process. One common multiservice network on which voice, data and video applications operate provides great benefits to enterprises. In this thesis, enabling technologies for voice, data, video integration are discussed. Features of voice, data, video applications, emerging interoperability standards, market segments are addressed. Finally financial benefits of voice, data and video integration technologies are explained by the help of a real-life project.
Keywords: Veri iletim sistemleri